Photoprotective Activity of Topsentin, A Bis(Indole) Alkaloid from the Marine Sponge Spongosorites genitrix, by Regulation of COX-2 and Mir-4485 Expression in UVB-Irradiated Human Keratinocyte Cells - Jiyoung Hwang; Donghwa Kim; Jae Sung Park; Hyen Joo Park; Jongheon Shin; Sang Kook Lee (Marine Drugs, 2020)
Skin is an important barrier to protect the body from environmental stress. However, exposure to ultraviolet radiation (UV) and various environmental oxidative stresses can cause skin inflammation. Cyclooxygenase-2 (COX-2) is an inducible enzyme that mediates the formation of prostaglandin E2 (PGE2) against internal and external inflammatory stimulations. Therefore, the inhibition of COX-2 is an important approach to maintain skin health and prevent skin inflammation and carcinogenesis. Topsentin, a bis(indolyl)imidazole alkaloid isolated from the marine sponge Spongosorites genitrix, has been reported to exhibit anti-tumor and anti-microbial activities. However, the effect of topsentin on skin inflammation and its underlying molecular mechanism has not been elucidated. In the present study, we identified the photoprotective effects of topsentin on UVB irradiated human epidermal keratinocyte HaCaT cells. Topsentin suppresses COX-2 expression and its upstream signaling pathways, AP-1 and MAPK. Furthermore, topsentin inhibits miR-4485, a new biomarker selected from a microarray, and its target gene tumor necrosis factor alpha induced protein 2 (TNF-α IP2). The photoprotective effect of topsentin was also confirmed in a reconstructed human skin model. These findings suggest that topsentin may serve as a potential candidate for cosmetic formulations with skin inflammatory-mediated disorder.